Analysis of Carbon Emissions in ASEAN Manufacturing: Input-Output and Panel Data Approach - Kartiasih, Fitri; Sandi, Imella Mendita; Abioga, Naufal Raffie; Aditya, Randy Daffa; Sabrina, Rizka (Efficient: Indonesian Journal of Development Economics, 2025)
This research aims to identify the leading sectors in four ASEAN countries and analyze the influence of production in these sectors and the consumption of renewable energy on carbon dioxide emissions in these countries. The analytical methods used include the analysis of inter-sector linkages and identifying leading sectors using input-output tables, followed by further analysis with panel data regression. The results indicate that while the leading sectors vary among the four countries, the manufacturing sector predominantly leads. Additionally, GDP in the manufacturing sector and renewable energy consumption significantly affect carbon dioxide emissions in the four ASEAN countries